2013
DOI: 10.1186/1471-2334-13-473
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of routine testing of individuals with HIV indicator diseases in order to prevent late HIV diagnosis

Abstract: BackgroundThe aim of our work was to evaluate the potential impact of the European policy of testing for HIV all individuals presenting with an indicator disease, to prevent late diagnosis of HIV. We report on a retrospective analysis among individuals diagnosed with HIV to assess whether a history of certain diseases prior to HIV diagnosis was associated with the chance of presenting late for care, and to estimate the proportion of individuals presenting late who could have been diagnosed earlier if tested wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
4
35
0
5
Order By: Relevance
“…In a recent prospective study looking at the effectiveness of indicator condition-guided testing for HIV, Sullivan et al 22 found an HIV prevalence of 1.8% (95% CI 1.42% to 2.34%) across European centres, similar to our estimate of 2.7% (95% CI 1.1% to 4.4%). Furthermore, findings from an analysis from 13 counselling and testing sites in Italy indicated that those presenting late with HIV were probably already infected at the time their initial indictor disease was diagnosed, but that there was a median lapse of 22.6 months between indicator disease diagnosis and HIV diagnosis 23. The lack of adherence to guidelines in this group therefore is likely to be hindering timely identification of HIV greatly.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study looking at the effectiveness of indicator condition-guided testing for HIV, Sullivan et al 22 found an HIV prevalence of 1.8% (95% CI 1.42% to 2.34%) across European centres, similar to our estimate of 2.7% (95% CI 1.1% to 4.4%). Furthermore, findings from an analysis from 13 counselling and testing sites in Italy indicated that those presenting late with HIV were probably already infected at the time their initial indictor disease was diagnosed, but that there was a median lapse of 22.6 months between indicator disease diagnosis and HIV diagnosis 23. The lack of adherence to guidelines in this group therefore is likely to be hindering timely identification of HIV greatly.…”
Section: Discussionmentioning
confidence: 99%
“…La cifra mediana de linfocitos CD4 en nuestro estudio en el momento del diagnóstico fue 303/mm 3 , el 55% de los pacientes tuvieron un DT según la nueva definición europea y el 16% habían alcanzado un estadio sida en el momento en el que la infección fue diagnosticada. Este porcentaje tan elevado de DT es el publicado también en otros estudios recientes (españoles 2,3 y de otros países europeos 12,13 ) que utilizaron la misma definición. Mientras que hace 20 años, en ausencia de tratamiento, la trascendencia de un retraso en el diagnóstico era mínima a nivel individual, hoy en día se traduce en una pérdida de oportunidades para el tratamiento, con un impacto directo en el pronóstico del paciente infectado, además de para la disminución de la propagación de la infección.…”
Section: Discussionunclassified
“…En varios estudios previos se ha documentado que el DT afecta fundamentalmente a varones 3,4 , a UDVP o infectados por transmisión heterosexual [2][3][4]12 , a inmigrantes (en especial latinoamericanos y subsaharianos) [2][3][4]12,13 , y que aumenta con la edad [2][3][4]12,13 . Los argumentos utilizados para explicar el incremento del riesgo de DT con la edad han sido varios: una menor percepción del riesgo por parte de pacientes y de profesionales sanitarios conforme aumenta la edad 13,14 , una diferente historia natural de la enfermedad con una evolución más rápida en los pacientes de mayor edad 15 o bien, simplemente ser debido a que los pacientes más jóvenes han vivido menos años tras la infección y han tenido por lo tanto menor posibilidad de desarrollar DT que los mayores 1 . La interacción encontrada en nuestro estudio entre la edad y el origen del paciente (en los españoles el riesgo de DT aumenta con la edad pero esto no se observa en los inmigrantes) apoyaría esta última explicación porque los pacientes originarios de países donde la prevalencia de la infección es mayor adquieren la infección en edades más jóvenes y las diferencias entre las cohortes de nacimiento tienden a diluirse.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A large Italian cohort showed the importance of testing for HIV following the diagnosis of HIV indicator conditions, as this significantly decreases the probability of late HIV diagnosis 20. A UK general practice case–control study found that 25.8% of HIV cases had presented with one or more HIV indicator conditions 1 year prior to receiving a diagnosis of HIV 21.…”
Section: Discussionmentioning
confidence: 99%